Development, Implementation, and Evaluation of a New Course on Essential Skills for Women's Leadership in Global Health - Anna Kalbarczyk; Elizabeth Hood; Luthfi Azizatunnisa; Utsamani Cintyamena; Frehiwot Nigatu; Prativa Baral (Ubiquity Press, 2022)
While many calls have been made to support the development of women leaders in global health, few resources have been developed and evaluated to meet this goal. We developed and evaluated a one week online short course on the essential skills for women's leadership in global health, offered in June 2021 to 22 students from 4 countries (Australia, Ethiopia, Thailand, and the United States). The course covered the state of women's leadership in global health and influencing factors; leadership theories models and frameworks; self-awareness and self-assessments; organizations and enabling environments; communication; and negotiation, and was designed to promote skills via practice, discussion, and debrief. Students rated the course highly and enjoyed the skills-building components, diversity of voices presented throughout the course, and embedded networking opportunities. Future iterations of the course, particularly those held in low-and middle-income countries, should contextualize materials, co-create with local instructors and amplify local voices, and consider incorporating shadowing, coaching, mentorship, and communities of practice.